Properties of isomaltulose (Palatinose®) – An emerging healthy carbohydrate: Effect of temperature and solute concentration - do Carmo, Juliana Rodrigues; Corrêa, Jefferson Luiz Gomes; Polachini, Tiago Carregari [UNESP]; Telis-Romero, Javier [UNESP] (Elsevier, 2022)
Isomaltulose (Palatinose®) is an emerging low glycemic and low insulinemic carbohydrate with several health benefits. Therefore, data about the properties (solubility (IS), density (ρ), specific heat capacity (cp), thermal conductivity (λ), and dynamic viscosity (µ)) of isomaltulose solutions in a wide range of temperature and concentrations are scarce. The influence of the temperature and solute concentration was evaluated by fitting empirical equations commonly applied for carbohydrate solutions to the experimental data. The generic polynomial model concerning the significant variables predicted the experimental values with good accuracy (R2 > 0.99; p < 3.91%). The µ showed an Arrhenius exponential-type behavior (R2 > 0.97; p < 8.02%). IS increase with temperature (T). The ρ and µ increased with isomaltulose concentrations (IC) and decreased with T. The cp and λ increased with T and decreased with IC. The availability of these properties covers a lack of data for the effective design of food processing equipment and unit operations such as osmotic dehydration, pumping, and pasteurization.
Keywords: Modeling; Solubility; Sucrose; Thermophysical properties; Viscosity